A New State-Dependent of Sliding Mode Control for Three-Phase Induction Motor Drives - Sulaiman , Marizan; Fizatul Aini, Patakor; Ibrahim, Zulkifilie (Praise Worthy Prize, 2013)
Abstract - Chattering is known as a main obstacle in realizing sliding mode control. In this study, new robust and chattering suppression of sliding mode control method is investigated. First, an integral sliding mode control is developed. Then, a simple smooth function and switching gain with state-dependent based on fast sigmoid function is introduced. This method allows chattering reduction, as well as maintaining the robust characteristics of sliding mode control. The effectiveness of the proposed algorithm is demonstrated using simulation speed control of indirect field-oriented three-phase induction motor drives with regard to external load disturbances.